MODELS OF STEM CELL NICHE structure REGULATION IN SHOOT APICAL MERISTEM - U. S. Zubairova; S. V. Nikolaev (Вавиловский журнал генетики и селекции, 2015)
The experimental data obtained to date provided grounds for certain concepts of the stem cell niche regulation in shoot apical meristem. Mathematical modeling is used for checking their consistency and coherence with experimental evidence. In this paper, we summarize mathematical models of stem cell niche regulation offered by different authors, analyze the experimental base and working hypotheses formalized in these models, and identify methodological differences in the approaches to the construction of these models.